Determinants of Online Impulsive Buying Post Pandemic Covid-19 - Andreani, Fransisca; Anastasia, Njo; Foedjiawati, Foedjiawati (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2023)
During the Covid-19 pandemic, the use of social media has increased in line with online buying transactions. This research was conducted to find out online impulsive buying due to the large amount of information and promotion spread on social media after the pandemic. Online questionnaires were distributed to 261 respondents who made online transactions. SEM-PLS 3.0. was used to analyze the data.  The results prove that hedonic browsing has a significant influence on flow experience. Flow experience has a significant influence on cognitive experience and affective experience as well as online impulsive buying. Cognitive experiences have significant influence on online impulsive buying. However, affective experiences do not have a significant influence on online impulsive buying. Moreover, financial management behavior cannot moderate the relationship among cognitive and affective experiences as well as online impulse buying. Theoretically, the study shows that irrational consumption processes lead to hedonic shopping due to easy and convenient searching for products through social media. Thus, in practice it is advisable for marketing managers to design their promotions on social media related to products and interspersed with financial literacy so that consumers can shop wisely.